Total Hydrocarbons in Water, Sediments and some Aquatic Plants at Al-Chibayish Marsh in Southern of Iraq - Al-Atbee, Rehab S.; Al-Hejuje, Makia M.; Al-Saad , Hamid T. (Mesopotamian Journal of Marine Sciences, 2024)
Concentration and distribution of total petroleum hydrocarbons in water, sediment and two merged aquatic plants species (Phragmites australis and Typha domingensis) have been detected. The samples were collected from four selected stations at Al-Chibayish marsh in Thi-Qar province, southern Iraq seasonally from August, 2017 to April, 2018. Spectroflurometer (Shimadzu-RF-540) was used for this purpose. Results showed that the lowest concentration in water was 1.91 µg/l recorded in summer season, whereas the highest concentration was 6.79 µ/l recorded in winter season. In sediments, the highest concentration 17.98 µg/g dry weight was recorded in winter season, while the lowest concentration was 2.98 µg/g dry weight was recorded in summer. The range of hydrocarbons concentrations in two aquatic plants species was 6.00-34.91 , 5.25-30.68 µg/g dry weight, for Phragmites austeralis, Typha demingensis respectively. The present study indicated that there are concentrations of hydrocarbons exist in the study area were the permissible range